Disease assessment and pathogenicity of Phomopsis spp. in fruits of eggplants (Solanum melongena) in Miagao, Iloilo, Philippines - AIVEE MAE B. NACIONALES; DIANA P. PAGUNTALAN (Nusantara Bioscience, 2026)
Abstract. Nacionales AMB, Paguntalan DP. 2026. Disease assessment and pathogenicity of Phomopsis spp. in fruits of eggplants (Solanum melongena) in Miagao, Iloilo, Philippines. Nusantara Bioscience 18 (1): n180102. https://doi.org/10.13057/nusbiosci/n180102. Fruit rot is an economically important disease affecting eggplant (Solanum melongena) production worldwide. This study assessed the incidence, severity, and economic impact of fruit rot in Barangay Oyungan, Miagao, Iloilo, Philippines and characterized its causal pathogen. Across three harvests, disease incidence averaged 35.05%, with 14.75% specifically attributed to fruit rot. The Percent Disease Index (PDI) was consistently high (mean 54.79%). Economic losses were substantial, with rejected fruit peaking at 51.55% of the harvest on 17 March 2024. Morpho-cultural characterization of fungal isolates revealed nine colonies, of which AES2R3 and AES3R3 exhibited typical Phomopsis spp. characteristics. AES2R3 produced both alpha- and beta-conidia, whereas AES3R3 produced only alpha-conidia. Pathogenicity tests confirmed that both isolates were pathogenic, producing characteristic sunken, gray-to-brown lesions and dark pycnidia by 22 days post-inoculation. These findings establish that Phomopsis spp. is a major cause of eggplant fruit rot in the locality and demonstrate its significant impact on yield and quality. Results highlight the importance of implementing integrated disease management strategies, varietal screening, and seasonal monitoring to reduce losses and support farmer profitability. This is the first study to report the occurrence of Phomopsis species causing fruit rot in Miagao, Iloilo.